Synergy of piracetam and aminalon in the cerebroprotective effect of olatropyl. - Mamchur, V. I.; Dronov, S. N. (Medicni Perspektivi, 2018)
Optimization of pharmacotherapy of neurological and psychosomatic diseases led to the creation of combined medicines containing two or more components with different mechanisms of action, differently affecting the pathogenesis and clinical manifestations of specific forms of pathology. Combined drugs that help normalize the central regulatory mechanisms of the development of somatic pathology, improve brain metabolism and hemodynamics, stabilize the cortical-subcortical relationships, the disorders of which lie at the base of many forms of neurological and psychosomatic pathology have been particularly popular in recent years. In this article we propose options for optimizing nootropic therapy with olatropyl, which is a combination of two "true" nootropics - gamma-aminobutyric acid (aminalone) and piracetam in one drug form. Such a combination allows one-stage implementation of a complex of multifaceted and diverse effects on the central nervous system characteristic of both piracetam and aminalone, but achieved through fundamentally different mechanisms of action of these agents. The mechanism of action of olatropil demonstrates the pronounced synergism of the monocomponents of the preparation. This combination allows to reduce the therapeutic dosages of each of the active substances by 2 times, which, in turn, leads to a decrease in the incidence and severity of possible side effects; leveling the exciting effect of piracetam and providing higher safety and efficacy. The drug is an effective tool for the therapy of various forms of cerebrovascular pathology, improving cognitive functions, mental activity, psychoemotional status, autonomic functions, favorably affecting the quality of life of patients. The uniqueness of the mechanism of action of olatropil, consisting in the occurrence of the fact of pharmacodynamic synergy in the combined use of piracetam and aminalone in a single dosage form, contributes to the enhancement of positive pharmacological effects and the leveling of a number of negative elements of pharmacodynamics of preparation constituents.